2004
DOI: 10.1191/0269215504cr737oa
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the sensory scale of the Fugl-Meyer Assessment in stroke patients

Abstract: The psychometric properties of the FMA-S in measuring sensory function do not support its clinical use in stroke patients. Further studies on methods to improve the psychometric properties of the FMA-S are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 23 publications
6
65
1
10
Order By: Relevance
“…However, there was also found a ceiling effect for the subscale sensitivity of the FMA protocol, as already documented in a previous study 18 . The significant ceiling effect of the NSA subscales may have happened due to the fact that the sample was composed by chronic hemiparetics with mainly motor deficits, which did not allow the confirmation of the NSA limitations in discriminating deficits of these patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, there was also found a ceiling effect for the subscale sensitivity of the FMA protocol, as already documented in a previous study 18 . The significant ceiling effect of the NSA subscales may have happened due to the fact that the sample was composed by chronic hemiparetics with mainly motor deficits, which did not allow the confirmation of the NSA limitations in discriminating deficits of these patients.…”
Section: Discussionsupporting
confidence: 86%
“…It evaluates the identification of weights and textures by hemiparetic subjects, however it is limited to the hand evaluation and does not involve thermal sensations and stereognosis 17 . The subscale of sensitivity of the Fugl-Meyer Assessment (FMA) of physical performance involves extereoception and proproception of the upper and lower limbs and has high inter-rater reliability and internal consistency, nevertheless it has shown a high ceiling effect and a poor to moderate reliability for the item extereoception 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sensory loss has a negative effect on personal safety, functional outcome, and quality of life, and it influences length of stay in hospital, highlighting the functional importance of training addressing these capacities 3) . Thus, stroke patients who have sensorimotor deficit show poor functional prognosis compared to those who have only pure motor deficit 4) . Unilateral spatial neglect, which appears most frequently in right inferior parietal lobe damage, is one of the common symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study concluded that the FM sensation subscale could not be recommended for clinical use because it showed significant ceiling effect and low validity and responsiveness to clinically meaningful change [49]. The ceiling effect implies that many patients attain full score without necessarily having intact sensation.…”
Section: Traditional Approachesmentioning
confidence: 99%